Long COVID in Children: Observations From a Designated Pediatric Clinic. Issue 12 (5th August 2021) - Ashkenazi-Hoffnung, Liat; Shmueli, Einat; Ehrlich, Shay; Ziv, Adi; Bar-On, Ophir; Birk, Einat; Lowenthal, Alexander; Prais, Dario
Abstract : Supplemental Digital Content is available in the text. Abstract : Systematic data are lacking on pediatric long COVID. This study prospectively assessed 90 children with persistent symptoms who presented to a designated multidisciplinary clinic for long COVID. In nearly 60%, symptoms were associated with functional impairment at 1–7 months after the onset of infection. A comprehensive structured evaluation revealed mild abnormal findings in approximately half the patients, mainly in the respiratory aspect.